2022
DOI: 10.1055/s-0042-1757231
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Multiplex PCR for Detection of Mycobacterium tuberculosis Complex in Presumptive Pulmonary Tuberculosis Patients and Its Utility in Smear Negative Specimens

Abstract: Objective The primary objective of this study was to assess the diagnostic performance of multiplex polymerase chain reaction (mPCR) for the detection of Mycobacterium tuberculosis complex (MTBC) in presumptive pulmonary TB patients, in the setting of a tertiary level teaching hospital in central India, in comparison to liquid culture using BACTEC mycobacteria growth indicator tubes (MGIT) 960 TB system as the gold standard. The secondary objective was to assess the performance of mPCR for Ziehl Neelsen smear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Contrarily, the same study also reported that the sensitivity ranged between 32 and 92% depending on the type of sample and the type of study design. Another study demonstrated that the performance of an IS6110 sequence-based PCR on AFB smear-negative sputum was 64.5% (Lodha et al, 2022). In addition, another previous study revealed that IS6110-TaqMan assay performed better sensitivity than GeneXpert MTB/RIF on AFB smear-negative sputum (69 vs. 48%, 19), while another study demonstrated GeneXpert MTB/RIF had a sensitivity level of 73.1% compared to culture (Lombardi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, the same study also reported that the sensitivity ranged between 32 and 92% depending on the type of sample and the type of study design. Another study demonstrated that the performance of an IS6110 sequence-based PCR on AFB smear-negative sputum was 64.5% (Lodha et al, 2022). In addition, another previous study revealed that IS6110-TaqMan assay performed better sensitivity than GeneXpert MTB/RIF on AFB smear-negative sputum (69 vs. 48%, 19), while another study demonstrated GeneXpert MTB/RIF had a sensitivity level of 73.1% compared to culture (Lombardi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity of these molecular techniques in smear-negative PTB remains relatively low. 34 Previous studies have reported sensitivities of 57.1% for Xpert MTB/RIF and 53.4% for CapitalBio Mycobacterium RT-PCR for detecting smear-negative PTB, 2 indicating the need for further improvement. Although the sensitivity of Xpert MTB/RIF ultra for smear-negative PTB has improved, 31 it is still unsatisfactory.…”
mentioning
confidence: 98%